2016
DOI: 10.1590/0034-7167.2016690307i
|View full text |Cite
|
Sign up to set email alerts
|

Úlcera por pressão em pacientes críticos: incidência e fatores associados

Abstract: RESUMENObjetivo: identifi car la incidencia y describir los factores asociados con las úlceras de presión en pacientes críticamente enfermos. Métodos: es un estudio de cohorte prospectivo con 77 pacientes, uso clínico, metabólico y factores asociados a la evaluación de las úlceras de presión, la aplicación de las escalas de riesgo (Braden y Waterlow) y clasifi cación en categorías de las úlceras. Resultados: se encontró una incidencia del 22% (IC del 95%: 12.6-31.5), y el 17 con 32 úlceras por presión en la re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
4
46

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 14 publications
9
37
4
46
Order By: Relevance
“…However, it should be noted that the study cited did not include ICU in its sample, so it may not be considered a reliable standard of comparison, but it certainly can be interpreted as a north for improvement. Regarding the location of injuries in the sample (Table 4), he highest concentration (76.5%) of PI in the sacral region is an aspect of wide agreement in the literature 8,[10][11][12][13] . In addition to the fact that the second largest portion of PI involvement occurred in the scapular region of the patients, it can be inferred that the skin care of the back, although not exclusive, should be a factor of attention to the health team and, mainly of nursing of the ICU researched.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…However, it should be noted that the study cited did not include ICU in its sample, so it may not be considered a reliable standard of comparison, but it certainly can be interpreted as a north for improvement. Regarding the location of injuries in the sample (Table 4), he highest concentration (76.5%) of PI in the sacral region is an aspect of wide agreement in the literature 8,[10][11][12][13] . In addition to the fact that the second largest portion of PI involvement occurred in the scapular region of the patients, it can be inferred that the skin care of the back, although not exclusive, should be a factor of attention to the health team and, mainly of nursing of the ICU researched.…”
supporting
confidence: 70%
“…Again, the fact that the hospitalization pro le of the sample investigated was not mainly of clinical order, that is, the common pro le of the elderly population in the hospital system. erefore, it is interpreted that the largest portion of the patients served in the service was not elderly, they were treated in the ICU due to trauma and external causes, which may have also re ected in the average length of stay in the ICU lower than other studies, in which the mean age of the patients was higher 10,13 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In hospitals, patients with pressure ulcers had a mean age of 65.3 years. Similarly to the study in brazil by Borghardt et al (2016) (40) who found that the incidence of pressure ulcers among critically ill patients in this study was 22%, with length of stay, type of hospitalization, The age variable was not statistically significant in this investigation; however, a median of advanced age (60 years) was observed, especially in the group of patients with PU, in patients older than 60 years, according to Sayar et al (2009) (41) and Cox (2011) (42) .…”
Section: A Study In Turkey By Tweed and Tweed (2008)mentioning
confidence: 72%
“…Patients without PI had a median Braden risk score of 14 (variation from 8 to 20); 68% of these patients had moderate risk of developing PI (P = 0.003) [23]. …”
Section: Discussionmentioning
confidence: 99%